Pravopisna stikanja Razprave o pravopisnih vprašanjih - Dobrovoljc, Helena; Jakop, Nataša (ZRC SAZU, Založba ZRC, 2012)
The purpose of the treatise is to present arguments for supplementing and changing orthographic rules and, at the same time, for confirming their adequacy. It is particularly questions on language use raised in public that draw attention to flaws in existing rules, to problems with interpreting them and to new, not yet recorded uses. The treatise comprises findings of 18 authors.